Organic Extract Effectiveness of Chaya Leaf (Cnidoscolus aconitifolius) to Corn Cob Borer Mortality - Rusli Rustam; Farha Safhira Puti (Agrotechnology Research Journal, 2025)
The decrease in corn crop yields in Riau Province was possibly caused by several factors, one of which was the infestation of plant pests such as the corn cob borer (Helicoverpa armigera Hubner). The primary choice for farmers to control H. armigera was using synthetic insecticides, but this could lead to various negative impacts. A solution to reduce the use of synthetic insecticides was the utilization of botanical insecticides, such as those derived from the leaves of chaya (Cnidoscolus aconitifolius I. M. Johnst). This research was conducted with the aim of determining the effective concentration of chaya leaf organic extract against corn cob borer larvae mortality in laboratory conditions. The experiment was conducted in a completely randomized design (CRD) with 5 treatments, each replicated 4 times, totaling 20 experimental units. Each experimental unit consisted of 10 third-instar H. armigera larvae. The concentrations of chaya leaf organic extract used were 0%, 0.25%, 0.50%, 0.75%, and 1%. Parameters observed included initial mortality time, lethal time 50 (LT50), lethal concentration 50 and 95 (LC50 and LC95), daily mortality rate and total mortality. The results indicated that the concentration of 0.75% of chaya leaf organic extract was effective in controlling H. armigera larvae. It caused a total mortality of 82.50%, with an initial mortality time of 6.25 hours and a lethal time 50 (LT50) of 29.75 hours after application.